(untitled) (Vietnam Journal of Agriculture and Environment, 2022)
This study was conducted to identify the initial freezing point temperature (tf) of water and to investigate the changes of thermophysical properties of snakehead fish muscle during the chilling process. The temperatures of snakehead fish muscle during the chilling process and tf identification decreased from 25.7°C to 0.5°C, and from 28.3°C to -8.2°C, respectively. The result indicated that the initial freezing point temperature (tf) of water in the snakehead fish muscle was -1.3°C. The temperature of snakehead fish muscle affected considerably the thermophysical properties of snakehead fish muscle. The density (r) and specific heat (c) increased with decreasing temperature during the chilling process. Inversely, the thermal conductivity (k), thermal diffusivity (a) and enthalpy (h) decreased with decreased temperature. The results obtained from this study could be applied in calculating the energy requirements and equipment used in snakehead fish processing industry.